Enantioselective nickel-catalyzed arylative intramolecular 1,4allylations - Nguyen, Thi Le Nhon; Incerti-Pradillos, Celia A.; Lewis, William; Lam, Hon Wai (Royal Society of Chemistry, 2018)
The enantioselective nickel-catalyzed desymmetrization of allenyl cyclohexa-2,5-dienones by reaction with arylboronic acids is described. Nickel-catalyzed arylation of the allene gives allylnickel species, which undergo cyclization by 1,4allylation to produce hexahydroindol-5-ones and hexahydrofuran-5-ones with three contiguous stereocenters in high diastereo- and enantioselectivities.